Performance of micro gas turbine trigeneration system and photovoltaic hybrid based system in remote area applications - Mohamad Rizdwan, Rashid Chand (2020)
The technological advancements in power generation are primarily undertaken to overcome the drawbacks of conventional energy system while diversifying energy sources to ensure sustainability in future power generation. One of the alternatives proposed is to implement a hybrid system combining both photovoltaic and micro gas turbine in a trigeneration scheme, the PV-MGT(TGS) hybrid system. Basically, it is a distributed energy system that is capable of producing electricity, hot water and cooling air simultaneously. The system integrates various components including micro gas turbine, photovoltaic, heat exchanger, hot and chilled water storage, absorption chiller and auxiliaries’ components such as boiler and batteries. Although there were several studies conducted on analyzing the performances of PV-MGT(TGS) hybrid system for urban residential and office application, however, there is lack of existing studies describing performances of the respective system for remote area application. Thus, this research intended to analyze the performance of PV-MGT(TGS) hybrid system for remote area applications to ensure its feasibility for such applications. The main objectives of the research are to investigate the technical performances of PV-MGT(TGS) hybrid system for annual operation in remote area through simulations.as well as to analyze the energetic, economic and environmental performances of the hybrid system in a remote area application. The system is analyzed based on the performances obtained from an application-based simulation. Whereby, a resort located on Tioman Island is selected as the demand site. The energy data and weather data of the demand site are acquired through site visit survey, estimation tool and real-time monitoring system respectively. The mathematical model of each component in the hybrid system is derived from manufacturer’s data sheets, published experimental data and thermodynamic modeling. The simulations are performed in the Simulink® environment where the mathematical models, operation algorithms of the proposed dispatch strategy and collected data are integrated. The simulations are carried out on an hourly basis for 8760-hour period (1 Year). Subsequently, based on the simulation result, the energetic, economic and environmental performances of the hybrid system are evaluated through primary energy analysis, life cycle cost analysis and emission reduction index. The outcome of the research demonstrates that the PV-MGT(TGS) hybrid system are able to achieve 21.08% of primary energy saving than the conventional system throughout the year. It can be observed that the hybrid system achieved 81%, 57%, 75.6% of emission reduction of oxide of Nitrogen (NOx), carbon monoxide (CO) and carbon dioxide (CO2). as compared to the conventional system. However, the PV-MGT(TGS) hybrid system failed to achieve positive net profit under Life Cycle Cost Analysis.